Penerapan Digital Image Processing untuk Mendukung Kurikulum Abad 21 di Perguruan Tinggi Keagamaan Islam (PTKI) - Muhammad Arief Rochman (UIN Sunan Kalijaga Yogyakarta, 2021)
Digital image processing has been in a fast progress and used in many fileds. The use of the digital image processing in Islamic universities has not been widely used but only used in some deparments such as Computer Engineering, Electronic Engineering, and Medical Faculty. Meanwhile, digital image processing can be used to develop Arabic study and Islamic manuscript research. In Islamic education, it can be used to develop Arabic study to identify certain texts such as isim, fiíl and letters from image. And so is in Islamic manuscript research, digital image processing helps identifying certain fading text because of age. The objective of this study is to describe how to identify a text in Alquran digital image using processing software, digital image processing. Hopefully, this study can be used as a guidance for the following researches in language field and ancient Islamic manuscript in Islamic Universities. This study uses Normalized Cross Correlative methods. This method give correlation value between -1 until 1, where 1 indicate that two have same the exact same shape. This study use the word Allah in Alquran Utsmani as an object sample that will be detected. It uses Python language programming to apply the methods. The main library used here is OpenCV. The experiment has detected the text of the word Allah in Alquran image with 90% average of similarity. The application of Digital image processing can be used for Islamic studies, especially in Arabic study and Islamic manuscript research. The application of Digital Image Processing skill can support the development of the 21st Curricullum in Islamic universities.